Global software piracy, technology and property rights institutions - Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
This study extends the literature on fighting software piracy by investigating how Intellectual Property Rights (IPRs) regimes interact with technology to mitigate software piracy when existing levels of piracy are considered. Two technology metrics (internet penetration rate and number of PC users) and six IPRs mechanisms (constitution, IPR law, main IP laws, WIPO Treaties, bilateral treaties and multilateral treaties) are used in the empirical analysis. The statistical evidence is based on: (i) a panel of 99 countries for the period 1994-2010 and (ii) interactive contemporary and non-contemporary Quantile regressions.The findings show that the relevance of IPR channels in the fight against software piracy is noticeably contingent on the existing levels of technology embodied in the pirated software. There is a twofold policy interest for involving modern estimation techniques such as interactive Quantile regressions. First, it uncovers that the impact of IPR systems on software piracy may differ depending on the nature of technologies used. Second, the success of initiatives to combat software piracy is contingent on existing levels of the piracy problem. Therefore, policies should be designed differently across nations with high-, intermediate- and low-levels of software piracy.
Keywords: F42; K42; O34; O38; O57; 330; Piracy; Business Software; Software piracy; Intellectual Property Rights